Retracted: Enhanced protective properties and UV stability of poly(lactic acid)/poly(vinyl acetate)/ZnO microcapsule nanocomposite. Issue 1 (15th September 2017) - Zhang, Bin; Han, Jian
Abstract : Zhang, B. and Han, J. (2019), Enhanced protective properties and UV stability of poly(lactic acid)/poly(vinyl acetate)/ZnO microcapsule nanocomposite. J Vinyl Addit Technol, 25: 68‐75. doi:10.1002/vnl.21604 . The above article from the Journal of Vinyl & Additive Technology, published online on 15 September 2017 in Wiley Online Library (wileyonlinelibrary.com ), has been retracted by agreement by the authors, the Journal Editor‐in‐Chief Alan Lesser, and Wiley Periodicals, Inc. The retraction has been agreed upon following the explanation by corresponding author Bin Zhang that this article contained irreproducible results. After efforts to replicate and adjust the enlarge test, the authors found misleading scientific content in Figures 2b, 4, 6, 8, 9b, and 11c‐d based on incorrect comparisons to prior work in the journal Fibers & Polymers as follows: Zhang B, Han J. Preparation and UV‐protective property of PVAc/ZnO and PVAc/TiO2microcapsules/poly(lactic acid) nanocomposites. Fibers and Polymers, 2016, 17(11):1849‐1857. DOI10.1007/s12221‐016‐6, 679‐1 .